In vitro reactivation of acetylcholinesterase using the oxime K027 - Kuca, Kamil; Kassa, Jirí (Veterinary and human toxicology, 2004)
The ability of a new bisquaternary oxime, K027 (1-[4-hydroxyiminomethylpyridinium]-3-[carbamoylpyridinium] propane dibromide), to reactivate the enzyme acetylcholinesterase (AChE) inhibited by the nerve agents Tabun, sarin and VX was evaluated. Its reactivation potency was compared to the AChE reactivators pralidoxime (2-PAM), obidoxime and HI-6; K027 seems a good reactivator of organophosphates-inhibited AChE. Its reactivation potency is lower compared to the other oximes for reactivation of sarin-inhibited AChE, but it is sufficient to significantly increase the activity of sarin-inhibited AChE. Its reactivation ability is comparable to obidoxime for reactivation of VX- and tabun-inhibited AChE and is higher than the reactivation potency of HI-6, for tabun-inhibited AChE. HI-6 is currently regarded the most promising reactivator of organophosphates-inhibited AChE.
Keywords: Dose-Response Relationship, Drug; pyridinové sloučeniny; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; Organothiophosphorus Compounds; obidoxim chlorid; Pralidoxime Compounds; sarin; Sarin; Cholinesterase Inhibitors; Oximes; Obidoxime Chloride; organothiofosforové sloučeniny; Pyridinium Compounds; organofosfáty; zvířata; vztahy mezi strukturou a aktivitou; pralidoximové sloučeniny; Organophosphates; Structure-Activity Relationship; oximy; reaktivátory cholinesterasy; Animals